Tutorial Action in Small Groups: An Educational Experience With University Students - Vladimir Essau Martínez-Bello; Ángela Martínez.Rojas (Universidad Nacional, Costa Rica, 2016)
This study establishes three objectives. The first, describe the main characteristics of a tutorial action program developed within an academic subject in a Faculty of teacher training. The second, determine the level of appraisement of the degree of importance given by students to a group of transversal skills and the kowledge level related to the research methodology during the tutorial action. The third, discuss the role of the tutorial action at the university in the new European Higher Education Area. The experience was developed in the academic year 2014-2015. Thirty six students participated and constructed two ad-hoc questionnaires. Four elements can be highlighted from the analysis of results: the interaction between participants, the perceived organization and the tutorial action methodology, the positive assessment to the development of skills related to research, and the development of critical attitude. As conclusion, it is considered that showing the process of construction and development of the tutorial action as an alternative experience in higher education and teacher training subjects, can help to clarify alternative pedagogical mechanisms to facilitate communication and participatory processes consistent with the new European Higher Education Area.